THE INFLUENCE OF LOCATION, PRICE AND QUALITY OF SERVICE ON CONSUMER REPURCHASE INTEREST - Ian Zulfikar (Jurnal Ekonomi, 2022)
Currently, the development of the culinary industry in the Bandung region is exhibiting extremely quick growth; consequently, a suitable marketing plan is required. This study aimed to examine the impact of location, pricing, and service quality on the repurchase intentions of Bu Imas Bandung Restaurant consumers. This study employs a quantitative methodology and an associative research design, with analysis performed using the Multiple Linear Regression test and SPSS 25.0 for Windows. Results indicated that location has a positive and statistically significant influence on the intention to repurchase the Bu Imas Bandung Restaurant. (2) the price has a positive and significant influence on the desire to repurchase the Bu Imas Restaurant Bandung; and (3) the service quality has a positive and large influence on the intention to repurchase the Bu Imas Restaurant Bandung. (4) The location, pricing, and quality of service have a positive and significant effect on the intention to repurchase the Bu Imas Restaurant Bandung